Synthesis, Characterization of Cu, S doped TiO2 and Its Photocatalytic Activity for Degradation of Remazol Black B - Abdul Haris; Gunawan Gunawan; Didik Setiyo Widodo; Rahmad Nuryanto; Retno Ariadi Lusiana; Mei Viantikasari (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
Copper and sulfur modified TiO2(Cu-S-TiO2) photocatalyst was successfully synthesized using TiCl4, Cu(NO3)2.3H2O and H2SO4 as precursors by the sol-gel method andcalcination at 450°C for 4 hours. The synthesized photocatalyst was characterized by X-Ray Diffraction (XRD), Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS), Diffuse Reflectance Spectroscopy (DRS), Brunauer Emmett Teller (BET) method. The XRD results showed that the Cu-S-TiO2 photocatalyst had an anatase phase with a crystal grain size of 17.54 nm. However, the SEM image of the modified TiO2 showed inhomogeneous phase due to the crystal clustering of imperfect homogenization during the synthesis and sintering processes. The patterns of EDSof Cu-S-TiO2depicted the elements of Ti, O, Cu and S with doping of Cu and S c.a. 7 and 1%, respectively. Analysis using DRS UV-Vis showed Cu-S-TiO2 was able to shift the absorption of the TiO2 photocatalyst wavelength to the visible region with a band energy gap of 1.9 eV. The BET analysis results showed that the specific surface area (SBET), pore volume (Vp) and average pore volume radius (Dp) were measured from large Cu-S-TiO2, therefore Cu-S-TiO2 had good physicochemical and photocatalytic properties. The photocatalytic activity of 0.1 g Cu-S-TiO2 with 15 Watt tungsten light irradiation for 4 h was able to degrade 50 mL remazol black B 10 mg/L c.a. 92.60 %.